(untitled) (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
The article deals with the phenomenon of translating political-economic knowledge in Napoleonic Italy. It focuses on translation as a tool for defining knowledge and constructing national identities. In particular, the author examines the role of peritexts. The analysis of prefaces, introductions, and notes provides a specific perspective on the relationship between the original and the translation, reflecting on the role of the translator (or the editor) in appropriating the original text, even to the point of expressing his own ideas and pursuing certain cultural and political goals. These paratexts permit a reading of the debates and an understanding of the importance attached to economics as a knowledge of government, revealing the value attributed to translation as a tool for constructing a new society.